The role of the teaching practice in undergraduate medical education: A perspective from the United States of America. Issue 3 (1st September 2018) - Fetters, Michael D.; Rew, Joanna; Heidelbaugh, Joel J.
Abstract : This article describes and reflects on the role of teaching practices in undergraduate medical education on the basis of teaching experience in the United States of America. China in particular, but also other family medicine–emerging countries, continues to embark on a path of creating and embracing a family medicine–centric system. The purpose of this article is to provide a US perspective on teaching priorities and strategies for medical students, and how these fit into a larger structure of the family medicine clinical clerkship. We emphasize knowledge, clinical skills, clinical behaviors, and strategies for succeeding as a preceptor. We introduce key aspects of the University of Michigan family medicine clerkship and the highly effective structure provided by the leadership of the course directors. This organizational structure provides a framework for implementing the family medicine clerkship for teaching medical students. As China and other family medicine–emerging countries increasingly embrace the discipline, we hope these ideas will provide a meaningful reference. Significance statement: Despite the growth of family medicine for more than 50 years in many countries, there remain many family medicine–emerging countries that have limited experience in the teaching of family medicine to medical students. This article provides suggestions for specific educational practices when one is teaching a medical student engaged in a clinical clerkship. Specifically, it focuses on both what to teach and how to teach family medicine–relevant clinical skills, knowledge, and behaviors to a medical student during a clinical rotation. Moreover, the article includes a series of formative and summative evaluation forms that are used at the University of Michigan that have content similar to the formats used in many US medical student training programs and that can be adapted for use in other settings.